Pengaruh Delayed Cord Clamping terhadap Kadar Hemoglobin (HB) dan Hematokrit (HT) pada Bayi - Bunga Tiara Carolin; Suprihatin Suprihatin; Ami Damayanti (Jurnal Sehat Mandiri, 2020)
The main serious problem in Indonesia is anemia, this is a major nutritional problem in children in Indonesia. The incidence of iron deficiency anemia in term infants 0-6 months is 40.8%. One of the efforts to deal with anemia in infants and toddlers is by delaying the clamping and cutting of the center because the newborn is still getting a blood transfusion from the placenta around 100 ml. The Objective to determine the effect of delaying cord clamping and cutting on hemoglobin (Hb) and hematocrit (Ht) levels in infants at Utama Anny Rahardjo Clinic. This research is an experimental research with posttest only control group design. The population in this study were all babies born from May - July 2019. Sampling in the study with purposive sampling so that 15 respondents were obtained as the control group and 15 respondents as the experimental group. Data analysis uses independent t-test. The mean Hb and Ht levels of the control group were 15.033 gr/dl and 46.25% and the mean in the experimental group was 19.332 gr/dl for Hb and Ht 59.11%. The results of the analysis by independent t-test obtained a significance value 0,000. The Conclusion there are differences in Hb and Ht levels in infants with immediate and delayed cord cutting and clamping.